Gerhardtia yunnanensis (Agaricales, Lyophyllaceae), a new species from southwest China - Mu, Man; Huang, Hong-Yan; Huang, Ting; Yang, Shu-Da; Tang, Li-Ping (Phytotaxa, 2021)
Gerhardtia yunnanensis is described as a new species from southwestern China. The species is characterized by its medium to large basidiomata with a yellow-brown to reddish brown pileus with a translucent-striate pale margin, weakly curved stipe, basidia with both cyanophilic and siderophilic reactions, basidiospore walls having a cyanophilic reaction, basidiospores with minute granular or verruculose ornamentation under SEM, narrowly clavate to irregular or curved clavate cheilocystidia and pleurocystidia, and absence of clamp connections. A comparison of all taxa of the genus was performed based on morphological and ITS and LSU molecular data. Furthermore, we provide a key to the known species of Gerhardtia worldwide.